2007
DOI: 10.1111/j.1742-1241.2006.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic analysis of antimicrobial therapy of chronic obstructive pulmonary disease exacerbations

Abstract: The aim of the study was to analyse the clinical and economic indicators of the treatment of acute exacerbations of chronic obstructive pulmonary disease (COPD). The study focused specifically on antimicrobial therapy and the use of fluoroquinolones in the management of exacerbations. Data on the consumption of antibiotics to treat exacerbations in ambulatory care were derived from IMS Health. Also, an observational, retrospective analysis was carried out of patients who entered the clinical pathway for COPD e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
1
7
0
2
Order By: Relevance
“…Similar to previous studies, economic costs of hospitalisations due to exacerbations were high [6][7][8][9][10]. These findings indicate that the COPD exacerbations requiring hospitalisation have a great impact on healthcare costs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to previous studies, economic costs of hospitalisations due to exacerbations were high [6][7][8][9][10]. These findings indicate that the COPD exacerbations requiring hospitalisation have a great impact on healthcare costs.…”
Section: Discussionsupporting
confidence: 88%
“…Simoens et al [9], using a symptom-based exacerbation definition, followed 267 patients in Belgium and found the median cost of hospital treatment to be €5143 (7757$) per exacerbation. Hospital stay was 75% of the total costs.…”
Section: Discussionmentioning
confidence: 99%
“…The literatures reports that the estimated costs for hospitalization due to acute exacerbation will range from $5,655 to $7,413 in developed countries [37][38][39]. The reduced frequency (27.2%) of acute exacerbation in the PV+IV group in this study, compared to the IV group, has significant economic implications for patients with COPD.…”
Section: Discussionmentioning
confidence: 80%
“…In this study, the total cost of hospitalization due to COPD exacerbations was found to be $808. Previous studies have reported a wide range of cost per hospitalization (between $612 and $9,545) 5–7,1924…”
Section: Discussionmentioning
confidence: 99%